Treatment with Brivanib alaninate as a second-line monotherapy after Sorafenib failure in hepatocellular carcinoma: A case report. Issue 10 (March 2019) - Zhu, Hong; Zhang, Chunyan; Yang, Xi; Yi, Cheng
Abstract: Rationale: Hepatocellular carcinoma (HCC) is one of the most frequent causes of cancer-related death worldwide. Its poor prognosis is due to the high invasiveness of the disease and limited efficacy of available treatments. Patient concerns: We reported an HCC patient who developed lung metastases 1 year after HCC resection. Sorafenib was then initiated; however, disease progression was noted 3 months later. Sorafenib therapy was initially maintained due to lack of effective alternatives, but disease progression continued. Diagnoses: HCC patient with lung metastases, and pulmonary portal, and mediastinal lymph node metastases (stage IVB). Interventions: Brivanib alaninate was used alone as second-line therapy. Outcomes: All metastases showed increased size on radiographic imaging approximately 3 months after brivanib alaninate was initiated. However, 2.5 months later, the lung metastases significantly decreased in size or disappeared. The pulmonary portal, and mediastinal lymph node metastases also significantly decreased in size. At 9.5 months after brivanib alaninate initiation, the pulmonary portal, and mediastinal lymph node metastases nearly disappeared, and the lung metastases continued to decrease in size. Alpha fetoprotein (AFP) level showed the same change pattern as the tumor-response observed on radiographic imaging. The total duration of brivanib alaninate treatment was 11 months, which was stopped due to repeated grade 2 thrombocytopenia. The other side effects were tolerable. Fifteen months after initiation of brivanib alaninate, the patient remained in very good condition without evidence of disease progression. Lessons: Brivanib alaninate alone as second-line therapy showed excellent antitumor efficacy for an HCC patient with numerous lung and lymph node metastases. It may exert its antitumor effects in a delayed-onset fashion. We suggest that patients receive brivanib alaninate for a long duration to fully determine its efficacy.